Temperature dependent response of microcystin-LR in acclimated M. aeruginosa PCC 7806 - Pierre-Louis Lalloué; Clarisse Mallet; Alexandre Bec; Apostolos-Manuel Koussoroplis; Fanny Perrière; Delphine Latour (Harmful Algae, 2026)

Ectotherm Size‐ and Age‐At‐Maturity in a Warmer, Variable and Resource‐Poor World - Nathan Frizot; Alexandre Bec; Apostolos‐Manuel Koussoroplis (Ecology Letters, 2025)
Ectotherms tend to mature at smaller sizes as average temperatures rise, a pattern known as the Temperature‐Size Rule (TSR), which also predicts earlier age at maturity. However, in natural environments, warming is often accompanied by increased thermal variability and limited nutritional resources. Using a bioenergetic model combined with factorial growth experiments on Daphnia , we investigated how temperature, food concentration, and food quality (Polyunsaturated fatty acid and sterol content) jointly shape size and age at maturity. We find that poor food quality narrows the upper thermal limit for TSR expression, while low food quantity restricts both upper and lower thermal bounds. Increased thermal variability shifts this range towards cooler temperatures. These findings suggest that the TSR may not hold under ecologically realistic conditions, especially when organisms are close to their thermal optimum where small concomitant increases of resource limitation and temperature variability with warming may lead to smaller yet older individuals at maturity.

Aquatic ectotherms under global warming: The hidden role of anaerobic processes in metabolic response - Marine Escura; Thomas Ruiz; Alexandre Bec; Christian Desvilettes; Apostolos‐Manuel Koussoroplis (Limnology and Oceanography, 2025)
In a warming world, acclimation of metabolic rate in aquatic ectotherms has been pointed out as a critical process to offset the temperature‐induced increase of energy requirements and the associated higher oxygen demand. However, this paradigm is drawn from measurements of aerobic energy production as a proxy for metabolic rate, thus overlooking the contribution of anaerobic energy production. Here, we combined individual‐based respirometric and calorimetric measurements to assess the metabolic rate of the ubiquitous ectotherm Gammarus pulex , a key detritivore species severely impacted by warming of freshwater streams. We assess aerobic and total metabolism after a shift from an optimal temperature (12°C) up to a suboptimal temperature (22°C). We showed that exposure to warming decreases aerobic metabolic rate while total metabolic rate remains constant and is associated with higher lactate body content. Our finding suggests that the reduction of oxygen consumption reflects a shift to anaerobic processes rather than an overall metabolic decrease often referred to as metabolic compensation. Our results urge a critical assessment of anaerobic contribution to the thermal response of ectotherms at the level of populations and communities to enhance prediction of the response of aquatic populations under global change.

Food quality shapes gradual phenotypic plasticity in ectotherms facing temperature variability - Marine Van Baelen; Alexandre Bec; Erik Sperfeld; Nathan Frizot; Apostolos‐Manuel Koussoroplis (Ecology, 2024)
Organisms exhibit reversible physiological adjustments as a response to rapidly changing environments. Yet such plasticity of the phenotype is gradual and may lag behind environmental fluctuations, thereby affecting long‐term average performance of the organisms. By supplying energy and essential compounds for optimal tissue building, food determines the range of possible phenotypic changes and potentially the rate at which they occur. Here, we assess how differences in the dietary supply of essential lipids modulate the phenotypic plasticity of an ectotherm facing thermal fluctuations. We use three phytoplankton strains to create a gradient of polyunsaturated fatty acid and sterol supply for Daphnia magna under constant and fluctuating temperatures. We used three different fluctuation periodicities to unravel the temporal dynamics of gradual plasticity and its long‐term consequences for D. magna performance measured as juvenile somatic growth rate. In agreement with gradual plasticity theory, we show that in D. magna , fluctuation periodicity determines the differential between observed growth rates and those expected from constant conditions. Most importantly, we show that diet modulates both the size and the direction of the growth rate differential. Overall, we demonstrate that the nutritional context is essential for predicting ectotherm consumers' performance in fluctuating thermal environments.

The energetic cost of facing cyanotoxins: a case study on Daphnia magna - Thomas Ruiz; Apostolos-Manuel Koussoroplis; Delphine Latour; Alexandre Bec (Aquatic Ecology, 2023)

Utilization of basal resources in a forested headwater stream: a combined stable isotope and fatty acid approach - Tiphaine Labed-Veydert; Alexandre Bec; Fanny Perrière; Christian Desvilettes (Aquatic Sciences, 2023)

Nutritional context modulates the salinity tolerance of freshwater invertebrates - Thomas Ruiz; Apostolos-Manuel Koussoroplis; Vincent Felten; Alexandre Bec (Aquatic Ecology, 2022)

Upstream/downstream food quality differences in a Caribbean Island River - Lou Frotté; Alexandre Bec; Cédric Hubas; Fanny Perrière; Sébastien Cordonnier; Etienne Bezault; Dominique Monti (Aquatic Ecology, 2022)

Early spring food resources and the trophic structure of macroinvertebrates in a small headwater stream as revealed by bulk and fatty acid stable isotope analysis - Tiphaine Labed-Veydert; Apostolos-Manuel Koussoroplis; Alexandre Bec; Christian Desvilettes (Hydrobiologia, 2021)

Quantifying the energetic cost of food quality constraints on resting metabolism to integrate nutritional and metabolic ecology - Thomas Ruiz; Apostolos‐Manuel Koussoroplis; Michael Danger; Jean‐Pierre Aguer; Nicole Morel‐Desrosiers; Alexandre Bec (Ecology Letters, 2021)
Consumer metabolism controls the energy uptake from the environment and its allocation to biomass production. In natural ecosystems, available energy in food often fails to predict biomass production which is also (co)limited by the relative availability of various dietary compounds. To date, the link between energy metabolism and the effects of food chemical composition on biomass production remains elusive. Here, we measured the resting metabolic rate (RMR) of Daphnia magna along ontogeny when undergoing various (non‐energetic) nutritional constraints. All types of dietary (co)limitations (Fatty acids, Sterols, Phosphorus) induced an increase in mass‐specific RMR up to 128% between highest and lowest quality diets. We highlight a strong negative correlation between RMR and growth rate indicating RMR as a promising predictor of consumer growth rate. We argue that quantifying the energetic cost imposed by food quality on individual RMR may constitute a common currency enabling the integration of nutritional and metabolic ecology.

U‐shaped response Unifies views on temperature dependency of stoichiometric requirements - Thomas Ruiz; Apostolos‐Manuel Koussoroplis; Michael Danger; Jean‐Pierre Aguer; Nicole Morel‐Desrosiers; Alexandre Bec (Ecology Letters, 2020)
Temperature and nutrient availability, which are major drivers of consumer performance, are dramatically affected by global change. To date, there is no consensus on whether warming increases or decreases consumer needs for dietary carbon (C) relatively to phosphorus (P), thus hindering predictions of secondary production responses to global change. Here, we investigate how the dietary C:P ratio optimising consumer growth ( TER C:P : Threshold Elemental Ratio) changes along temperature gradients by combining a temperature‐dependent TER C:P model with growth experiments on Daphnia magna . Both lines of evidence show that the TER C:P response to temperature is U‐shaped. This shape indicates that consumer nutrient requirements can both increase or decrease with increasing temperature, thus reconciling previous contradictive observations into a common framework. This unified framework improves our capacity to forecast the combined effects of nutrient cycle and climatic alterations on invertebrate production.

Comparison of sterol and fatty acid profiles of chytrids and their hosts reveals trophic upgrading of nutritionally inadequate phytoplankton by fungal parasites - Mélanie Gerphagnon; Ramsy Agha; Dominik Martin‐Creuzburg; Alexandre Bec; Fanny Perriere; Cecilia Rad‐Menéndez; Claire M.M. Gachon; Justyna Wolinska (Environmental Microbiology, 2019)
Summary Chytrids are ubiquitous fungal parasites in aquatic ecosystems, infecting representatives of all major phytoplankton groups. They repack carbon from inedible phytoplankton hosts into easily ingested chytrid propagules (zoospores), rendering this carbon accessible to zooplankton. Grazing on zoospores may circumvent bottlenecks in carbon transfer imposed by the dominance of inedible or poorly nutritious phytoplankton (mycoloop). We explored qualitative aspects of the mycoloop by analysing lipid profiles (fatty acids, sterols) of two chytrids infecting two major bloom‐forming phytoplankton taxa of contrasting nutritional value: the diatom Asterionella formosa and the filamentous cyanobacterium Planktothrix agardhii . The polyunsaturated fatty acid composition of chytrids largely reflected that of their hosts, highlighting their role as conveyors of otherwise inaccessible essential lipids to higher trophic levels. We also showed that chytrids are capable of synthesizing sterols, thus providing a source of these essential nutrients for grazers even when sterols are absent in their phytoplankton hosts. Our findings reveal novel qualitative facets of the mycoloop, showing that parasitic chytrids, in addition to making carbon and essential lipids available from inedible sources, also upgrade their host's biochemical composition by producing sterols de novo , thereby enhancing carbon and energy fluxes in aquatic food webs.

A microcalorimetric approach for investigating stoichiometric constraints on the standard metabolic rate of a small invertebrate - Thomas Ruiz; Alexandre Bec; Michael Danger; Apostolos‐Manuel Koussoroplis; Jean‐Pierre Aguer; Jean‐Pierre Morel; Nicole Morel‐Desrosiers (Ecology Letters, 2018)
Understanding the determinants of metabolism is a core ecological topic since it permits to link individual energetic requirements to the ecology of communities and ecosystems. Yet, besides temperature, metabolic responses to environmental factors remain poorly understood. For example, it is commonly assumed that dietary stoichiometric constraints increase metabolism of small invertebrates despite scarce experimental support. Here, we used microcalorimetric measurements to determine the standard metabolic rate ( SMR ) of Daphnia magna fed stoichiometrically balanced (C/P: 166) or imbalanced (C/P: 1439). Daphnids fed imbalanced maintained their stoichiometric homeostasis within narrow boundaries. However, they consistently increased their SMR while decreasing their growth rate. Our measurements demonstrate that homeostatic regulation implies higher metabolic costs, thereby reducing available energy for growth. We demonstrate that microcalorimetry is a powerful and precise tool for measuring small‐sized organisms’ metabolic rate, thus opening promising perspectives for understanding how environmental factors, such as nutritional constraints, affect organismal metabolism.

Additive effect of calcium depletion and low resource quality on Gammarus fossarum (Crustacea, Amphipoda) life history traits - Marc Rollin; Romain Coulaud; Michael Danger; Bénédicte Sohm; Justine Flayac; Alexandre Bec; Arnaud Chaumot; Olivier Geffard; Vincent Felten (Environmental Science and Pollution Research, 2018)

Temporal changes in essential fatty acid availability in different food sources in the littoral macrophyte zone - Hélène Masclaux; Gilles Bourdier; Lionel Jouve; Emilie Duffaud; Alexandre Bec (Hydrobiologia, 2014)

Resource partitioning among cladocerans in a littoral macrophyte zone: implications for the transfer of essential compounds - Hélène Masclaux; Gilles Bourdier; Pascal Riera; Martin J. Kainz; Lionel Jouve; Emilie Duffaud; Alexandre Bec (Aquatic Sciences, 2014)

How pollen organic matter enters freshwater food webs - Hélène Masclaux; Marie-Elodie Perga; Maiko Kagami; Christian Desvilettes; Gilles Bourdier; Alexandre Bec (Limnology and Oceanography, 2013)
Huge amounts of pollen can accumulate at the air‐water interface during the floral bloom of wind‐pollinated trees. We hypothesized that such pollen rains act as subsidy pulses, promoting the development of a neustonic microbial food web and the transfer of pollen organic carbon to aquatic consumers. During a pine pollen rain event on an oxbow lake, microorganism concentrations were by far higher in the neuston, where pollen grains accumulated, than in the seston. Zooplankton species were also unevenly distributed in the two compartments. Bulk isotope and isotopes of fatty acid analyses revealed trophic partitioning among these zooplankton species, with some of the taxa foraging specifically on neuston, where they benefit from pollen‐derived carbon. Microorganisms were identified as a key element in the trophic upgrading of pollen food quality and in the transfer of pollen carbon to metazoan consumers. Pollen rains may thus contribute, as an allochthonous food pulse, to aquatic production at specific seasons, but they may also act as a structuring factor in lake habitats.

Food quality of anemophilous plant pollen for zooplankton - Hélène Masclaux; Alexandre Bec; Maiko Kagami; Marie-Elodie Perga; Telesphore Sime-Ngando; Christian Desvilettes; Gilles Bourdier (Limnology and Oceanography, 2011)
Pollen rain can lead to considerable allochthonous particulate organic carbon input into freshwater systems. However, the importance of allochthonous pollen deposition for zooplankton production has not so far been considered. Here, standardized growth experiments were performed to assess the quality of pollen from three species ( Alnus sp., Populus sp., and Cedrus sp.) as a food source for two cladocerans ( Daphnia longispina and Simocephalus vetulus ). Although lipid analysis revealed high polyunsaturated fatty acid (PUFA) contents in pollen, both cladoceran species exhibited suboptimal development when directly fed on pollen (ranging from 0.2 d −1 to 0.3 d −1 ). The low food value of pollen was attributed to the presence of a refractory wall reducing its digestibility. In a second set of experiments, cladocerans were fed on a mixture of heterotrophic microorganisms (bacteria, chytrids, and protozoa) that had grown on pollen grains ( Cedrus sp.). The introduction of microorganisms as an intermediate trophic level resulted in cladoceran growth rates that were about double those obtained on pollen alone. Hence, our findings suggest that pollen carbon could sustain zooplankton growth indirectly, and highlight the key role of microorganisms, and especially of chytrids, in transferring and upgrading pollen PUFA to higher trophic levels.

Combined effects of food quality and temperature on somatic growth and reproduction of two freshwater cladocerans - HÉlène Masclaux; Alexandre Bec; Martin J. Kainz; Christian Desvilettes; Lionel Jouve; Gilles Bourdier (Limnology and Oceanography, 2009)
We investigated the effect of food quality on somatic growth and reproduction of zooplankton at different temperatures (12°C, 15°C, 20°C, and 25°C). Standardized growth experiments of two cladocerans, Daphnia magna and Simocephalus vetulus , were performed on (1) high‐quality food ( Cryptomonas sp.), (2) relatively low‐quality food ( Scenedesmus obliquus ), and (3) intermediate‐quality food ( Cryptomonas : Scenedesmus mixture). Food quality constraints on somatic growth and reproduction of the two cladocerans decreased with increasing temperature. For D. magna and for S. vetulus , differences between clutch size and growth rate of individuals fed on the three food sources were highly pronounced when they were reared at 12°C and 15°C; however, such differences decreased at 20°C and were negligible at 25°C. Variations in food quality constraints with temperature can be explained by the variability of dietary polyunsaturated fatty acids, such as eicosapentaenoic acid and stearidonic acid requirements of these cladocerans. We conclude that dietary constraints exerted by food quality for zooplankton development vary as a function of different temperature conditions.

Trophic upgrading of autotrophic picoplankton by the heterotrophic nanoflagellate Paraphysomonas sp. - Alexandre Bec; Dominik Martin-Creuzburg; Eric von Elert (Limnology and Oceanography, 2006)
We investigated whether trophic repackaging of autotrophic picoplankton by phagotrophic protists is associated with an improvement in food quality for the metazooplankton Daphnia magna (i.e., whether trophic upgrading occurs in this system). The nutritional value of the autotrophic species Microcystis aeruginosa PCC7806, Synechococcus sp. strain BO8809, Synechococcus elongatus SAG 89.79, and Choricystis minor KR1988/ 8, and of the heterotrophic nanoflagellate Paraphysomonas sp. grown on these different picoplanktonic species was evaluated in standardized growth experiments with D. magna . In order to investigate the functional role of the flagellate in the simplified autotrophic picoplankton‐ Daphnia food chain, Paraphysomonas sp. was grown on the different picoplanktonic organisms and subsequently separated from the food items before being fed to D. magna. The presence of Paraphysomonas sp. as an intermediary trophic step enhanced somatic growth and reproduction of D. magna. Supplementation of Synechococcus sp. with lipids from Paraphysomonas sp. (grown on Synechococcus sp.) revealed that trophic upgrading of autotrophic picoplankton is due to the additional lipids present in the flagellate. Paraphysomonas sp. synthesized polyunsaturated fatty acids and sterols de novo, which most likely explains the trophic upgrading. Paraphysomonas sp. also improved the food quality of M. aeruginosa PCC7806, which is toxic for D. magna . The heterotrophic flagellate Paraphysomonas sp. is capable of trophically upgrading a poor quality food source not only by producing essential lipids, but also by detoxifying the cyanobacterial food organism.